Biomining - Rawlings, Douglas E.; Johnson, D. Barrie (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Biomining is the biotechnology that uses microorganisms to recover metals, in particular copper and gold, from ores and concentrates. Having developed from a very simple operational (in terms of both engineering and biology) process, biomining has developed into a multifaceted technology, to the extent that many of the largest industrial stirred tanks and heaps throughout the world are employed for bioprocessing minerals. This book has a strong applied approach and describes emerging and established industrial processes, as well as the underlying theory of the process, and the biology of the microorganisms involved. Chapters have been written by personnel from leading biomining companies, consultants and internationally recognized researchers and academics.